Three phase hollow fiber liquid-phase microextraction combined with HPLC-DAD/MS for simultaneous determination of tamoxifen and clomiphene from human urine, plasma and water samples - Yamini, Yadollah; Jönsson, Jan Åke; Zarghampour, Fereshteh (Journal of Chromatography A, 2025)
In this research, a straightforward and effective preconcentration technique was developed by integrating three-phase hollow fiber liquid-phase microextraction (HF-LPME) with high-performance liquid chromatography equipped with a photodiode array detector and mass spectrometry (HPLC-DAD/MS) for the simultaneous extraction and quantification of trace levels of tamoxifen (Tam) and clomiphene (Clom) in human urine, plasma, and natural water samples. In three-phase system, the target analytes are transferred from an aqueous matrix across an organic solvent and subsequently into an aqueous receiving phase. This approach provides an easy, selective, and cost-effective replacement for conventional sample preparation methods. The entirety of partitioning operations was accomplished using an Accurel Q3/2 polypropylene hollow fiber membrane. The optimized conditions included undecane as the impregnated organic solvent on polypropylene HF, 0.005 M NaOH as the source phase, 0.01 M HCl as the receiving phase, a stirring rate of 1000 rpm, and an extraction time of 75 min. Additionally, the calibration curves exhibited linearity within the range of 2.5–100 μg L⁻¹ using HPLC-DAD and within 0.1–10 μg L−1 and 15–100 μg L−1 using HPLC-MS, with good coefficients of determination (R² > 0.998). In the end, the practicality of the proposed method was confirmed through the extraction and quantification of the analytes in real samples, including human urine, plasma, and natural water. The results demonstrated excellent sensitivity and precision in detecting trace amounts of Tam and Clom across various matrices.
Publisher Copyright: © 2025
Keywords: Clomiphene; Hollow fiber liquid phase microextraction; HPLC-DAD; HPLC-MS; Tamoxifen